Lixo, coleta seletiva e reciclagem - Holzer, Gisele dos Santos Augusto (2013)
The advent of the Industrial Revolution to modern society starts to experience new perspectives consumption and purchasing goods produced in increasingly larger scales and lower prices. Linked to this, the promotion of consumerism has caused numerous environmental problems, because each time consumes more and sometimes without which focuses on the continuous disposal of solid waste. If this process does not occur properly, ie, wastes are not disposed of in landfills, the environmental impacts become even greater. As a result, the research developed aims to discuss the influences of trash in modern society as well as the processes needed to reduce the impacts. For this, the consequences will be highlighted the development of educational work where students realize the importance of recycling adopting the habit of practicing proper separation of waste produced at school and in their homes. The research methodology used to achieve these goals was based on analyzes bibliographic's Thematic Trash, Waste Recycling and Recycling and implementation of the project with students from 6th grade of elementary school in State College Arnaldo Busatto, located in the city of Foz do Iguaçu, Paraná. The development of this work provided students acquire knowledge about the various aspects of the issue and seek to reflect on the changing habits in the separation of waste generated in schools and in homes. The results could be evidenced by the active participation of a practical activity of making objects by using recycled materials and questionnaire answered by the students who participated in the project development.